The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1021/jo991556b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,1-Linked Galactosyl Mannosides Carrying a Thiazine Ring as Mimetics of Sialyl Lewis X Antigen:  Investigation of the Effect of Carboxyl Group Orientation on P−Selectin Inhibition

Abstract: This paper describes the synthesis of 1,1-linked galactosyl mannosides as sialyl Lewis X mimetics that contain a spiro-ring to position the carboxylate group in a well-defined orientation. It was found that compound 4 is more active as a P-selectin inhibitor (IC50 = 19 microM) than the parent disaccharide 2, which contains a flexible carboxyl group (IC50 = 193 microM). This result is consistent with that observed in the previous NMR study of sialyl Lewis X bound to P-selectin. The chemistry described here shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
(14 reference statements)
0
11
1
Order By: Relevance
“…[54] Starting from Shibuta et al reported the preparation of two diastereomeric 1,1-linked galactosyl mannosides possessing a spiro-thiazine ring, which act as sialyl Lewis mimetics. [55] For example, when the unprotected ulo-disaccharide 94 was coupled with S-cysteine (Sch. 18), in the absence of an acid catalyst, diastereomer 95 was obtained in good yield.…”
Section: Carbohydrate-based Molecular Scaffoldingmentioning
confidence: 99%
“…[54] Starting from Shibuta et al reported the preparation of two diastereomeric 1,1-linked galactosyl mannosides possessing a spiro-thiazine ring, which act as sialyl Lewis mimetics. [55] For example, when the unprotected ulo-disaccharide 94 was coupled with S-cysteine (Sch. 18), in the absence of an acid catalyst, diastereomer 95 was obtained in good yield.…”
Section: Carbohydrate-based Molecular Scaffoldingmentioning
confidence: 99%
“…One approach in the regulation of sLe x ‐selectin binding is the development of small molecule mimetics of sLe x which can act as selectin antagonists 5–14. An attractive lead compound is the 1,1‐linked disaccharide 2 , which is reported to be five and forty times more active than sLe x against E‐ and P‐selectin, respectively, in a cell‐based assay 15,16. The design of 2 was based on a sLe x ‐selectin binding model, and it was suggested that the galactose and mannose segments mimic the galactose and fucose residues in sLe x , respectively (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to elaborate the functional groups, together with the rigid molecular structure, render carbohydrates well suited as molecular templates to display pharmacophoric groups in well defined spatial orientation. Steric and conformational aspects play an important role in drug action, since the correct orientation of the different pharmacophoric group is necessary for the interaction with *Address correspondence to this author at the Department of Biotechnology and Biosciences, University of Milano-Bicocca, I-20126 Milano, Italy; Tel: (39)02-6448-3457; Fax: (39) 02-6448-3569; E-mail: Francesco.Nicotra@unimib.it specific receptors. As a matter of fact in organic bioactive compounds a rigid core, to which the different functional groups are covalently linked, has the function of providing this orientation.…”
Section: Introductionmentioning
confidence: 99%